T30. Sural nerve conduction studies in differentiation of hereditary and inflammatory demyelinating polyneuropathies. (May 2018) - Sorensen, Daniel; Vaeth, Signe; Fuglsang-Frederiksen, Anders; Andersen, Henning; Jensen, Uffe Birk; Tankisi, Hatice
Abstract : Introduction: Nerve Conduction Studies (NCS) are invaluable tools for diagnosis and classification of polyneuropathies. However, differentiation of different types of demyelinating polyneuropathies may sometimes be difficult. Detection of demyelination and differentiation of inflammatory and hereditary polyneuropathies are mainly based on motor NCS. We aimed in this study to examine the role of sural nerve sensory NCS in differentiation of inflammatory and hereditary polyneuropathies. Methods: Nineteen patients with chronic demyelinating polyneuropathy (CIDP), 16 patients with Guillain Barre syndrome (GBS) and 23 patients with hereditary motor sensory neuropathy with PMP22 duplication were included. In all patients, sural nerve was examined unilaterally or bilaterally with surface electrodes (13 patients) or near nerve technique (45 patients). In case of bilaterally examined sural nerves, right side was chosen for analysis. Results were compared to laboratory controls. The pathophysiological state of sural nerve was classified as normal, axonal loss or demyelinating according to ESTEEM criteria (Tankisi et al., 2005). Results: The mean conduction velocity (CV) was higher in CIDP (42.6 ± 5.6) and GBS (46.5 ± 8.1) than patients with PMP22 duplication (22.5 ± 5.3) ( p  < 0.001). The mean amplitude for GBS patients (11.2 ± 9.4) was higher than patients with CIDP (4.2 ± 4.9) and PMP22 duplication (3.0 ± 4.5) (p < 0.001). Sural sensory CV could distinguish all patients with PMP22 duplication (CV < 30 m/s) than CIDP (CV > 35 m/s). Sural NCS showed demyelination in all patients with PMP22 duplication and in 2 GBS whereas none of the CIDP patients had demyelination of the sural nerve. Normal sural nerve was seen in 10 GBS and in 5 CIDP patients whereas sural NCS showed axonal loss in 4 GBS and in 14 CIDP. Conclusion: Sural NCS may help in differentiation of inflammatory and hereditary demyelination polyneuropathies. Demyelinating changes in sural nerve are characteristic for PMP22 duplication whereas axonal loss is mostly seen in CIDP and normal sural nerve NCS in GBS.